A Comodulation Analysis of Atmospheric Energy Injection Into the Ground Motion at InSight, Mars. Issue 4 (22nd April 2021) - Charalambous, C.; Stott, A. E.; Pike, W. T.; McClean, J. B.; Warren, T.; Spiga, A.; Banfield, D.; Garcia, R. F.; Clinton, J.; Stähler, S.; Navarro, S.; Lognonné, P.; et al.
Abstract: Seismic observations involve signals that can be easily masked by noise injection. For the NASA Mars lander InSight, the atmosphere is a significant noise contributor, impeding the identification of seismic events for two‐thirds of a Martian day. While the noise is below that seen at even the quietest sites on Earth, the amplitude of seismic signals on Mars is also considerably lower, requiring an understanding and quantification of environmental injection at unprecedented levels. Mars' ground and atmosphere are a continuously coupled seismic system, and although atmospheric functions are of distinct origins, the superposition of these noise contributions is poorly understood, making separation a challenging task. We present a novel method for partitioning the observed signal into seismic and environmental contributions. Atmospheric pressure and wind fluctuations are shown to exhibit temporal cross‐frequency coupling across multiple bands, injecting noise that is neither random nor coherent. We investigate this through comodulation, quantifying the synchrony of the seismic motion, wind and pressure signals. By working in the time‐frequency domain, we discriminate between the different origins of underlying processes and determine the site's environmental sensitivity. Our method aims to create a virtual vault at InSight's landing site on Mars, shielding the seismometers with effective postprocessing in lieu of a physical vault. This allows us to describe the environmental and seismic signals over a sequence of sols, to quantify the wind and pressure injection and estimate the seismic content of possible marsquakes with a signal‐to‐noise ratio that can be quantified in terms of environmental independence. Finally, we exploit the relationship between the comodulated signals to identify their sources. Plain Language Summary: InSight put the first seismic station on the surface of another planet in 2019. While it has made the first detection of marsquakes, the wind has been providing a strong background signal that most of the time makes seismic detection difficult. This work aims to separate out the unwanted injection from Mars' atmosphere to give us confidence that the signals observed by InSight are vibrations from the planet itself. The issue of atmospheric injection into the seismic signal was foreseen before the mission launch and InSight was equipped with wind and pressure sensors. However, no stable relationship is observed between the strength of the wind and the amplitude of the measured vibrations by InSights' seismometers. Also, we are mainly sensing the wind shaking the lander, which transmits vibrations to the ground under our seismometer. These complications have led us to use the measurements themselves to work out the strength of the environmental injection rather than rely on a complex time‐varying model of the possible pathways. This work shows how we can work out estimates of how much the atmosphere is affecting the seismic measurements and in particular we show that the strongest possible quakes that have been detected by InSight are above what we might have expected from just the measurements from InSight's wind and pressure sensors at that time. Key Points: A comodulation analysis is implemented to describe and interpret the sensitivity of InSight's seismometers to atmospheric energy injection The seismic response of InSight to the wind and pressure is observed to vary diurnally and seasonally depending on atmospheric conditions The power from the wind and pressure signals injected into seismic events is quantified to assess marsquake discrimination